Study Of High Level Of Thinking Ability Of Class Xi Students At State Vocational School 4 Gorontalo - Risna S Tialo; Meyko Panigoro; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The purpose of this study was to describe the level of high-order thinking skills of class XI students in accounting subjects at SMK Negeri 4 Gorontalo. The research method used is a qualitative method. The objects in this study were students of class X1 with a total of 27 students. Data collection was carried out using a description test instrument consisting of 6 question items. The results showed that from the results of the PAP analysis, students' higher order thinking skills showed that from 27 students, 3 students (11%) had high HOTS thinking skills, 14 students (52%) had sufficient HOTS thinking skills, 1 student (4%) have low HOTS thinking ability, and 9 students (33%) have HOTS thinking ability.